Hubungan Kekuatan Otot Lengan Dan Kelincahan Dengan Kemampuan Menggiring Bola Siswa Ekstrakurikuler Bola Basket - Rosti Rosti; Jumaking Jumaking; Rizky Putri Aprilia (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The purpose of this study is to know the relationship between the independent variable and the dependent variable. Where the independent variables include arm muscle strength and also agility. The dependent variable is the ability to dribble. The type of research used in this research is quantitative research through the correlation method with the application of total sampling. The instruments used were the Push up test instrument, the shuttle run test and the zig zag dribbling test. The data were analyzed through prerequisite testing and hypothesis testing through the rule that: (1) there is a significant relationship between arm muscle strength and the ability to dribble a basketball with a correlation value of 0.691 which is included in the category of strong relationship level. (2) there is a significant relationship between agility and ability when dribbling a basketball with a correlation value of 0.544 which is included in the moderate relationship level category. (3) there is a simultaneous significant relationship to the three variables of arm muscle strength, agility, and ability to dribble with a correlation value of 0.691 which is included in the category of strong relationship level.